PENINGKATAN KEMAMPUAN BAHASA ARAB ANAK USIA DINI MELALUI IMPLEMENTASI MEDIA PERMAINAN EDUKATIF DI TKM AL-ASY’ARI SIDOARJO - Hasan, Laili Mas Ulliyah; Naseha, Siti Durotun; Hasan, Izzah Nur Hudzriyah (MAANA: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study investigates how the implementation of educational play media can improve Arabic language skills among early childhood learners at TKM Al-Asy’ari Sidoarjo. Using a qualitative descriptive method, the research explores children’s engagement, vocabulary development, and pronunciation accuracy during Arabic learning activities that incorporate flashcards, hijaiyyah puzzles, thematic board games, and recycled-material learning tools. The findings reveal that play-based media significantly enhance children’s participation, vocabulary retention, and confidence in speaking Arabic. The study highlights that effective implementation of play media, combined with teacher creativity and child participation in media-making, creates a joyful and meaningful learning experience, strengthening foundational Arabic skills in early childhood education. Keyword: Educational Play Tools, Arabic Learning, Eco-Participatory Learning.